2012
DOI: 10.4171/ggd/152
|View full text |Cite
|
Sign up to set email alerts
|

Pattern rigidity in hyperbolic spaces: duality and PD subgroups

Abstract: Abstract. For i = 1, 2, let G i be cocompact groups of isometries of hyperbolic space H n of real dimension n, n ≥ 3. Let H i ⊂ G i be infinite index quasiconvex subgroups satisfying one of the following conditions: 1) limit set of H i is a codimension one topological sphere. 2) limit set of H i is an even dimensional topological sphere.3) H i is a codimension one duality group. This generalizes (1). In particular, if n = 3, H i could be any freely indecomposable subgroup of G i . 4) H i is an odd-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…These papers used an action on a topological space and discreteness of the commensurator stemmed from the fact that the commensurator preserved a 'discrete geometric pattern' (in the sense of Schwartz, cf. [2,14,18,19]). In this paper we use an algebraic action from Chevalley-Weil theory and homological algebra as a replacement in order to conclude discreteness of the commensurator.…”
Section: The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers used an action on a topological space and discreteness of the commensurator stemmed from the fact that the commensurator preserved a 'discrete geometric pattern' (in the sense of Schwartz, cf. [2,14,18,19]). In this paper we use an algebraic action from Chevalley-Weil theory and homological algebra as a replacement in order to conclude discreteness of the commensurator.…”
Section: The Main Resultsmentioning
confidence: 99%
“…If Σ has finite genus and only finitely many punctures and no boundary components, then Σ has finite volume and so Γ is not thin. If Σ has a boundary component (that is, a flaring end), then Σ admits a proper geodesically convex core, in which case the limit set Λ Γ will be properly contained in ∂H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…, H n are cyclic. Biswas-Mj [BM08] generalize this to the case of subgroups which are either codimension one duality groups or odd-dimensional Poincare Duality groups or subgroups containing such subgroups as free factors.…”
Section: Givesmentioning
confidence: 99%
“…It is a classical fact that for real hyperbolic space H n , any Moebius map f : ∂H n → ∂H n extends to an isometry F : H n → H n . This fact is a crucial part of many rigidity theorems for hyperbolic spaces, for example the Mostow Rigidity theorem ( [Mos68]) and various "pattern rigidity" theorems ( [Sch97], [BM08], [Bis09]). More generally, Bourdon [Bou96] showed that if X is a rank one symmetric space of noncompact type (with the metric normalized so that the maximum of the sectional curvatures equals −1), and Y is any CAT(-1) space, then any Moebius embedding f : ∂X → ∂Y extends to an isometric embedding F : X → Y .…”
Section: Introductionmentioning
confidence: 99%